2016
DOI: 10.7860/jcdr/2016/18909.8194
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Evaluation of Sealing Ability of New MTA Based Sealers with Conventional Resin Based Sealer: An In-vitro Study

Abstract: IntrOductIOnThe goal of root canal obturation is to obtain a three dimensional seal of the root canal system. An inadequate filling during obturation can results in reentry and re-growth of microorganisms in the root canal system which irritates the periapical tissue and compromises the treatment success [1].To accomplish this many endodontic obturation materials and sealers are being used [2]. Guttapercha is a commonly used root canal filling material which is used with different types of endodontic sealers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Four studies were included for the assessment of apical microleakage [ 32 , 40 , 43 , 50 ] in mm with a total of 80 in the CSBs whilst 55 teeth in the RBS groups. Figure 6 demonstrates the forest plot using the random effect model showing standardised mean difference of 6.83 mm favouring the RBS [95% CI 2.90, 10.77] as well as showing statistically significant difference ( p = 0.0007) between these groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four studies were included for the assessment of apical microleakage [ 32 , 40 , 43 , 50 ] in mm with a total of 80 in the CSBs whilst 55 teeth in the RBS groups. Figure 6 demonstrates the forest plot using the random effect model showing standardised mean difference of 6.83 mm favouring the RBS [95% CI 2.90, 10.77] as well as showing statistically significant difference ( p = 0.0007) between these groups.…”
Section: Resultsmentioning
confidence: 99%
“…Investigating the solubility of CSBs is a major area for debate. In this respect, the superior or comparative sealing ability of the CSBs was reported [ 52 , 53 ], however Ahuja et al [ 50 ] demonstrated significantly high apical microleakage values for the CSBs resulting in a high standardised mean difference which favours the RBS. In addition, Al-Haddad et al [ 63 ] reported that RBS are slightly acidic and might result in self-etching when in contact with dentine, thereby enhancing interfacial bonding and adaptation with a reduction in the apical microleakage.…”
Section: Discussionmentioning
confidence: 99%
“…The improved sealing ability of MTA Fillapex is attributed to the setting mechanism of MTA which results in hydration of anhydrous mineral oxide compounds to produce calcium silicate hydrate and calcium hydroxide phases, which causes expansion thereby enhancing the seal and minimizing leakage. MTA fillapex shows an optimized flow due to presence of nanoparticles helping it to penetrate and fill lateral canals 24 .…”
Section: Discussion: -mentioning
confidence: 99%
“…Endosequence BC Sealer presented a superior sealing ability than AH Plus in a dye penetration evaluation 14 , consisting with the present results. In contrast, MTA Fillapex has demonstrated controversial sealing performance in endodontic literature 13,[15][16][17][18] , what may result from its physicochemical properties 19 and differences in experimental designs such as the evaluation technique.…”
Section: Discussionmentioning
confidence: 99%